Simulation and Measurement of Solar Harvesting Enhancement of Silver Plasmonic Nanoparticles on GaSb Nanodots. (24th March 2014) - Rosa, Lorenzo; Ranjan, Mukesh; Bhatnagar, Mukul; Mortazavi, Daryoush; Mukherjee, Subroto; Juodkazis, Saulius
Abstract : The performance of a plasmonic antireflection layer which can be utilized for deep-space radiationresistant GaSb solar cells is investigated numerically and experimentally. The layer consists of nanodots made by plasma etching of a GaSb substrate and subsequent physical vapor deposition of Ag nanoparticles on the nanodot tips, in a partially ordered configuration determined by the plasma energy level. This technique is readily applicable to patterning of silicon. We measure the substrate reflectivity and model the reflection and absorption of the substrates using the 3D finite difference time domain (FDTD) method, which are realistically imported as 3D layers from the scanning electron microscopy (SEM) images. The variation of the height of the Ag nanoparticles on top of the GaSb pillars shows that the plasmonic effect remarkably enhances the absorption. The presence of GaSb pillars enhances absorption and tunes the maximum absorption wavelength peak.